Implementation of the Comandos Application Accounting Information System at Bank BTPN Makassar Branch Office - Linda Arisanty Razak; Ainun Arizah; Amiruddin Husni (International Journal of Asian Business and Management, 2023)
This research is a type of research with case studies approach with the aim of knowing whether the application commands have been effectively applied to PT. Bank BTPN KC Makassar based on indicators of accounting information systems. Which method used in this study is a descriptive analysis. Technique data collection obtained through observation, documentation. the data that is obtained is secondary data and primary data. Based on the research results, the authors draw important conclusions, namely the application of commandos is very effectively implemented at PT. Bank BTPN KC Makassar. The Comandos app helps BTPN banks to become more efficient in managing and monitoring collateral data. This application is also well integrated with the existing system at Bank BTPN. The quality of the system produced by the Commandos application is very good and works optimally in processing customer data quickly and efficiently. The quality of the information generated by the Commandos application is also very good. Employees who use the Commandos application are very satisfied because the Commandos application is easy to understand, and especially easy to input data. After the application is updated the application performance gets better. Internal constraints use the application only on a network that is sometimes bad or slow